The gap between organisations understanding their tax risks and knowing their tax risks: from my experience at KPMG Bangladesh - Rahman, Rifa Saimah Bente (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.